I seek to express $DE$ and $UI$ and $IE$ in terms of $\theta$:

$$\sec { \theta } =DE+IE+UI \tag{1.1}\label{myeqone}$$ $$\frac { 1 }{ 4 } =UI(UI+IE) \tag{2.1}\label{myeqtwo}$$ $$(\frac { 1 }{ 2 } -\tan { \theta } )^{ 2 }=DE(DE+IE) \tag{3.1}\label{myeqthree}$$

I rewrote $(2)$ and $(3)$ as

$$\frac { 1 }{ 4 } =UI(sec\theta -DE) \tag{2.2}\label{myeqtwo_one}$$ $$(\frac { 1 }{ 2 } -{ tan }^{ 2 }\theta )=DE(sec\theta -UI) \tag{3.2}\label{myeqthree_one}$$

This is where I'm stuck. I tried solving the system by replacing $DE$ in $(2.2)$ with $$\frac { (\frac { 1 }{ 2 } -tan^{ 2 }\theta ) }{ (sec\theta -UI) } $$but to no avail. I've also tried multiplying, adding, and subtracting the two systems in the hopes of something symmetric or meaningful, but once again to no avail. I even replaced $UI$, $DE$, and $IE$ with $x$,$y$, and $z$ in the hopes of simplifying some notation and hopefully solving the equation, but to no avail.

  • 1
    $\begingroup$ The left-hand sides of $(3.1)$ and $(3.2)$ don't match. Which is correct? $\endgroup$ – Blue Oct 10 '19 at 0:53

Running this through Mathematica, I get ...

$$\begin{align} IE &= \pm\sqrt{\sin 2\theta} \\[4pt] UI &= \phantom{\sec\theta}-\frac12 \left(\pm\sqrt{\sin2\theta}-(\cos\theta+\sin\theta)\right)\\[4pt] DE &= \sec\theta-\frac12\left(\pm \sqrt{\sin2\theta}+(\cos\theta+\sin\theta)\right) \end{align}$$ where the same "$\pm$" is used throughout.

The algebra for deriving the above looks a bit messy; if you really want to see it, I can take a shot at writing it down. Personally, I'd like to see how the equations arose; there may be a straightforward geometric argument that avoids most of the algebra.

Here's what I did in Mathematica ...

Mathematica doesn't always simplify Sec[] and Tan[] the way I like, so I tend to write equations in terms of cost and sint, and then do a separate simplification pass. In this case, the crux of the work is done via:

Solve[{ 1/cost == DE + IE + UI, 1/4 == UI (UI + IE), (1/2 - sint/cost)^2 == DE (DE + IE)}, {DE, IE, UI}]


This gave two solutions (differing only in sign, hence the "$\pm$"), with this expression needing some attention:

Sqrt[cost^2 (-1 + sint^2) (-1 + cost^2 - 2 cost sint + sint^2)]

Without too much trouble, this simplifies to cost^2 Sqrt[2 sint cost]; that is, $\cos^2\theta \sqrt{\sin 2\theta}$. From there, a little clean-up gives the result as shown above.

  • $\begingroup$ Wow! How exactly did you run the equations through Mathematica? Can I see a screenshot so that I can try using it in the future? Thanks. In the future, I may work backwords and try to arrive at some geometric interpretation of these equations. $\endgroup$ – DarkRunner Oct 10 '19 at 0:35

For notational brevity, let $x=DE$, $y=IE$ and $z=UI$ and work with the set below,

$$x+y+z = \sec \theta \tag{1}$$ $$z(z+y) =\frac 14\tag{2}$$ $$x(x+y)=\left(\frac 12 -\tan\theta \right)^2\tag{3}$$

Take (3)-(2) and use (1),


From (3)+(2),

$$x^2+z^2+y(x+z)=\left(\frac 12 -\tan\theta \right)^2+\frac14\tag{5}$$

Square (1) and rearrange, $$y^2-(x-z)^2+2[x^2+z^2+y(x+z)]= \sec^2\theta\tag{6}$$

Substitute (4) and (5) into (6) to get the equation for $y$,

$$y^2-\sin^2\theta(\tan\theta-1)^2+2\left(\frac 12 -\tan\theta \right)^2+\frac12=\sec^2\theta$$

Then, simplify and obtain the solution for $y$,

$$y^2=\sin 2\theta,\>\>\>\>\>y=\pm\sqrt{\sin 2\theta}$$

Then, the solutions for $x$ and $z$ follow,

$$\begin{align} x&= -\frac12\left(y+\cos\theta+\sin\theta\right) +\sec\theta\\ z&= -\frac12 \left(y-\cos\theta-\sin\theta\right) \end{align}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.